O grupo: de espaço interacional à ferramenta de mediação - Clarindo, Janailson Monteiro (2015)
This study aimed to analyze the process of transition between two possible functions that a group assumes: an interactional symbolic space for its members and a meditational cultural tool. In the case of this second group conformation, their dynamics assumes the role of mediator instrument to the participants of the group. To achieve the goal above, the research used was influenced by the ethnography and took place in a Psychology class in the Federal University of Ceará (UFC), with participant observation during the entire semester and the video recording of four specific classes which were facilitated by the students themselves. The main theory used was the Historical-Cultural Psychology. Nineteen young adults of both genders students were both the discipline and research participants. In videotaped meetings, group dynamics were performed with various topics such as communication, competition and motivation. The examination of the video recordings were made through an interpretative analysis focusing on group functioning and characteristics that suggest evidence of the transition between the two functions assumed by the group. Theoretical analysis categories were the concepts of group and mediation. The empirical categories identified in the observation of the recordings was the relationship between competition and cooperation, and the awareness of the group process, observing the times when there was a transition between the group space interaction function to the mediating tool function. To this phenomenon was given the name of transition F1 - F2. The results indicate that the competition together with the cooperation in a group context favors the transition F1 - F2. Another factor that can leverage this transition arises from reflection and awareness of all the stages of group process.